Indicators of free radical oxidation in neutrophils of patients with primary and recurrent soft tissue sarcomas - I. A. Goroshinskaya; I. V. Kaplieva; E. M. Frantsiyants; L. N. Vashchenko; T. O. Lapteva; T. V. Ausheva; L. A. Nemashkalova; P. S. Kachesova; Yu. Yu. Kozel (Исследования и практика в медицине)
Purpose of the study. To carry out a comparative analysis of lipid peroxidation intensity and antioxidant system indices in blood neutrophils of patients with primary and relapsed soft tissue sarcomas (STS) depending on sex and age.Patients and methods. Of the 81 patients included in the study, 48 had primary STS, 5 patients with continued growth, and 28 patients with recurrent STS. The patients were divided by sex and age; the level of lipid peroxidation products, superoxide dismutase (SOD) activity, total peroxidase activity (TPA), glutathione peroxidase (GPx) activity and reduced glutathione (RG) content in blood neutrophils were investigated by conventional spectrophotometric methods. The comparison groups (donors) consisted of 12 men and 17 women divided into the same age subgroups: ≤ 45 years and > 45 years.Results. In donors, there was a multiple decrease in the SOD/TPA ratio with age, especially in women, and in men this was accompanied by an age-related decrease in GPx activity. In primary sarcomas in older women and in men with continued growth and recurrence, there was an increase in diene conjugates (DC). In men over 45 years of age, there was an increase in SOD, TPA, and GPx. Women of the older age group were characterized by activation of SOD and GPx, expressed in the relapsed process to a significantly greater extent than in men, and an increase in RG was observed in women. The increase in both components of the glutathione system and SOD activity was especially significant in the development of relapses in women for periods exceeding three years, which was accompanied by a decrease in DC content.Conclusions. Neutrophils are characterized by an increase in DC content in patients of both sexes in the older age group with primary and recurrent STS, with its highest content in men with continued growth and relapses. GPx activity, increased in both men and women in the older age group in all variants of STS development, may play an important role in the antioxidant protection of blood cells in STS. Thus, the most pronounced activation of GPx, accompanied by a maximum increase in reduced glutathione and activation of SOD, contributes to a decrease in the level of DC and the absence of MDA increase in women with slow development of recurrences.